2018
DOI: 10.1016/j.agee.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Maize stubble as foraging habitat for wintering geese and swans in northern Europe

Abstract: Agricultural crops have become increasingly important foraging habitats to geese and swans in northern Europe, and a recent climate-driven expansion in the area of maize fields has led to a rapid increase in the exploitation of this habitat. However, due to the novelty of maize foraging in this region, little is known about the abundance and energetic value of this resource to foraging birds. In this study we quantify food availability, intake rates and energetic profitability of the maize stubble habitat, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Such an increase has previously been shown by Nilsson & Persson (1992) who found that geese foraged on cereal stubble fields during autumn. The energetic return from spilled grain is substantial (Clausen et al 2018) and it should be an ideal food resource for geese at a time when they need to prepare physiologically for autumn migration . These results underline the importance of considering season when choosing crop type for a set-aside field.…”
Section: Discussionmentioning
confidence: 99%
“…Such an increase has previously been shown by Nilsson & Persson (1992) who found that geese foraged on cereal stubble fields during autumn. The energetic return from spilled grain is substantial (Clausen et al 2018) and it should be an ideal food resource for geese at a time when they need to prepare physiologically for autumn migration . These results underline the importance of considering season when choosing crop type for a set-aside field.…”
Section: Discussionmentioning
confidence: 99%
“…During the last few decades, most European goose populations have increased considerably (Fox and Madsen 2017), in response to a combination of improved conservation efforts and a shift in habitat use to energy-rich agricultural foods (Gauthier et al 2005, Fox and Abraham 2017, Clausen et al 2018. Growing numbers of geese in the landscape has led to increased foraging pressure on crops and competition with livestock (Olsen et al 2017, Petkov et al 2017.…”
mentioning
confidence: 99%
“…where M Bewick,Adult was the mean body mass of an adult Bewick's swan (6,000g; Kear, 2005), M S was the target mean body mass of the foraging swan species (Table 3), and a was the attack rate for Bewick's Swans feeding on sugar beet (0.00114 m 2 s -1 ; van Gils and Tijsen, 2007). The functional response equation for swans feeding on spilled maize (I Maize , in g DM hr -1 ), was scaled from the functional response for barnacle geese (Branta leucopsis) feeding on maize reported by Clausen et al (2018a):…”
Section: Swan Energy Gain and Expenditurementioning
confidence: 99%
“…Since the mid-twentieth century, agricultural land has supported increasingly large numbers of avian herbivores (Newton, 2017). High-energy crops can provide important food resources for herbivores, especially during winter when the availability of natural vegetation is low (Clausen et al, 2018a), but the types and spatial extent of crops available to herbivores vary both spatially and temporally due to environmental conditions as well as farming practices and economic incentives. Such food resources may be lost permanently to herbivores when fields are converted from agriculture to other uses, including housing and infrastructure (Döös, 2002).…”
Section: Introductionmentioning
confidence: 99%